The Potential Use of Forensic DNA Methods Applied to Sand Fly Blood Meal Analysis to Identify the Infection Reservoirs of Anthroponotic Visceral Leishmaniasis. - Ehud Inbar; Philip Lawyer; David Sacks; Daniele Podini (Public Library of Science (PLoS), 2016)
BACKGROUND:In the Indian sub-continent, visceral leishmaniasis (VL), also known as kala azar, is a fatal form of leishmaniasis caused by the kinetoplastid parasite Leishmania donovani and transmitted by the sand fly Phlebotomus argentipes. VL is prevalent in northeast India where it is believed to have an exclusive anthroponotic transmission cycle. There are four distinct cohorts of L. donovani exposed individuals who can potentially serve as infection reservoirs: patients with active disease, cured VL cases, patients with post kala azar dermal leishmaniasis (PKDL), and asymptomatic individuals. The relative contribution of each group to sustaining the transmission cycle of VL is not known. METHODOLOGY/PRINCIPAL FINDINGS:To answer this critical epidemiological question, we have addressed the feasibility of an approach that would use forensic DNA methods to recover human DNA profiles from the blood meals of infected sand flies that would then be matched to reference DNA sampled from individuals living or working in the vicinity of the sand fly collections. We found that the ability to obtain readable human DNA fingerprints from sand flies depended entirely on the size of the blood meal and the kinetics of its digestion. Useable profiles were obtained from most flies within the first 24 hours post blood meal (PBM), with a sharp decline at 48 hours and no readable profiles at 72 hours. This early time frame necessitated development of a sensitive, nested-PCR method compatible with detecting L. donovani within a fresh, 24 hours blood meal in flies fed on infected hamsters. CONCLUSION/SIGNIFICANCE:Our findings establish the feasibility of the forensic DNA method to directly trace the human source of an infected blood meal, with constraints imposed by the requirement that the flies be recovered for analysis within 24 hours of their infective feed.